Clinical value of motor function of digestive system investigation: past, present and future - A. S. Trukhmanov; O. A. Storonova; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To demonstrate modern methods of investigation of motor function of the esophagus, stomach, small and large intestine, anorectal area and their clinical value.Key points. First attempts to study qualitative and quantitative indicators of gastro-intestinal motor function were undertaken by clinicians in 80ies years of XIX century. Nowadays investigation of motor function of the esophagus can by carries out both by open catheter method (water perfused manometry), and by the newest hi-tech method – high resolution manometry (HRM) and volume 3D manometry. Combined recording of HRM and impedance allows to carry out differential diagnostics at belching, to detect aerophagy that helps to individualize treatment of the patient. The «gold standard» diagnostics of stomach motor disorders is radioisotope imaging. High resolution manometry allows to assess contractile function of pyloric part of the stomach, to reveal disorders of antroduodenal coordination. С13-octanoic acid breath test, ultrasound investigation, single-photon emission computed tomography, magnetic-resonance tomography are widely applied as well. Myoelectric activity of the stomach and small intestine can be analyzed by electrogastroenterography method. To study motor function of the colon and anorectal area defecography, intestinal transit time investigation with application of radioactive labels, balloon expulsion test, sphincter profilometry, large intestine manometry by solid-state catheter and other studies are performed. High resolution anorectal manometry is an up-to-date method of anorectal motor activity rating, that is practiced in specialized research centers. This method allows to estimate obturative function of rectal sphincter, intestinal component of stool continence.Conclusion. Clinical value of digestive system motor function investigation grows steadily and skill to diagnose disorders of peristaltic activity according to symptoms can and should be complemented by with modern methods of esophageal, gastric and intestinal motor activity registration.